2009
DOI: 10.4081/ijas.2009.761
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion of ClostridiumperfringensNetB positive strains in healthy and diseased chickens

Abstract: For over 30 years α toxin was considered the key virulence factor responsible for the appearance of necrotic enteritis (NE) in chickens but, recently, a new toxin related to the occurrence of NE, called NetB, has been described. The aim of this work was to evaluate the CP toxin-type and the NetB gene presence in strains collected from chickens affected or not by enteric diseases. 107 strains were tested: 30 isolated from chickens affected by NE, 54 from subjects affected by other enteric pathologies and 22 fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 7 publications
1
4
1
Order By: Relevance
“…Our study offers new insight regarding the prevalence of C. perfringens in Italian poultry flocks. As reported previously, 6 we confirmed the occurrence of netB- positive C. perfringens isolates in broiler flocks, with or without an enteric disorder, suggesting the need for additional environmental factors for disease development. Regarding turkey flocks, although we detected netB- positive C. perfringens isolates, the role of this organism in the pathogenesis of NE is still unclear.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…Our study offers new insight regarding the prevalence of C. perfringens in Italian poultry flocks. As reported previously, 6 we confirmed the occurrence of netB- positive C. perfringens isolates in broiler flocks, with or without an enteric disorder, suggesting the need for additional environmental factors for disease development. Regarding turkey flocks, although we detected netB- positive C. perfringens isolates, the role of this organism in the pathogenesis of NE is still unclear.…”
supporting
confidence: 91%
“…In Italy, an investigation carried out on 107 C. perfringens isolates recovered from broiler and commercial laying hen flocks revealed that 27% of isolates were netB positive, with 93% of these isolates coming from birds affected by intestinal disorders. 6 On the other hand, a similar study of 106 C. perfringens isolates from turkeys with enteric lesions failed to detect netB -positive isolates. 8…”
mentioning
confidence: 95%
“…In contrast, in a previous Italian survey on 107 CP isolates from diseased and healthy chickens, the netB encoding gene was detected in 93% of CP strains isolated from chickens with enteric disorders (Drigo et al, 2009).…”
Section: Discussioncontrasting
confidence: 64%
“…Necrotic enteritis (NE) is a devastating enteric disease, affecting different avian species, including broiler chickens, causing an estimated annual global economic loss of more than US$ 6 billion in the broiler industry (Wade and Keyburn, 2015). Although once the causative Clostridium perfringens strains are introduced into a flock most birds will be infected, not all will develop disease, if any (Drigo et al, 2009). Several studies mention isolation of C. perfringens NetB positive strains from healthy animals, clearly demonstrating a certain fraction of each flock is resistant to NE, also indicated by the lack of disease in a subset of birds in experimental models (Gholamiandekhordi et al, 2006;Drigo et al, 2009;Keyburn et al, 2010).…”
Section: Introductionmentioning
confidence: 99%